A Novel MPEG Audio Degrouping Algorithm and Its Architecture Design. (25th November 2010) - Tsai, Tsung-Han
Abstract : Degrouping is the key component in MPEG Layer II audio decoding. It mainly contains the arithmetic operations of division and modulo. So far no dedicated degrouping algorithm and architecture is well realized. In the paper we propose a novel degrouping algorithm and its architecture design with low complexity design consideration. Our approach relies on only using the addition and subtraction instead of the division and modulo arithmetic operations. By use of this technique, it achieves the equivalent result without any loss of accuracy. The proposed design is without any multiplier, divider and ROM table and thus it can reduce the design complexity and chip area. In addition, it does not need any programming effort on numerical analysis. The result shows that it takes the advantages of simple and low cost design. Furthermore, it achieves high efficiency on fixed throughput with only one clock cycle per sample. The VLSI implementation result indicates the gate counts are only 527.